Penelitian pengaruh plasticizer DOP terhadap sifat fisis slab kompon PVC untuk acuan sepatu - Rochani, Siti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1984)
DOP Plasticizer is a chemical substance which its function is to increase the plasticity of PVC compound slab.By adding DOP plasticizer can imporoves the impact resistance properties and decrease the hardness of slab. The utilization of 30% DOP results the greatest impact resistance (6,1016 kg/cm), and the hardness 55 shore A of PVC coumpund slab produced by this experiment.